PENGARUH FDR, NOM, BI RATE, INFLASI TERHADAP PRROFITABILITAS PT. BANK MUAMALAT INDONESIA, TBK - Bahirina Mujtaba (2022)
The growth of Islamic banks has increased every year, by having good performance, namely through an increase in profitability, this is able to contribute to improving the economy in Indonesia. But PT. Bank Muamalat Indonesia, Tbk (BMI) as the first Islamic bank in Indonesia, its profitability has decreased. So therefore, this study aims to determine the effect of financial and macroeconomic performance on the profitability of BMI 2012-2021 years. This study uses secondary data from BMI's financial statements using multiple linear regression analysis techniques. BMI's financial performance variables use the Financing to Deposit Ratio (FDR) and Net Operating Margin (NOM). While the macroeconomic variables are the BI Rate and Inflation. Then, profitability is shown using Return On Assets (ROA). The results of this study state that the variables FDR and NOM have a significant positive effect on the profitability of BMI, while the BI Rate has no effect on the profitability of BMI, and inflation has a negative effect on the profitability of BMI. The results of this study can contribute to the factors that influence profitability in the Islamic banking sector, especially from the internal side of the bank as well as the macroeconomic side.